2022
DOI: 10.3390/su14148729
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Media Credibility on Risk Perception of COVID-19 and the Sustainable Travel Intention of Chinese Residents Based on an Extended TPB Model in the Post-Pandemic Context

Abstract: This study is the first to examine the impact of media credibility on the sustainable travel intention of Chinese residents in the post-pandemic context. Specifically, the mechanisms by which media credibility influenced the sustainable travel intentions of Chinese residents through risk perception are studied. This study developed an extended theory of planned behavior (TPB) model and used a structural equation model (SEM) to analyze the 1219 valid samples received from online questionnaires. The results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 63 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…Online consumers prefer the visual demonstration of items, which makes those products appealing [ 69 ]. The relationship between attitude and intention is an extended application of the TPB [ 70 , 71 ]. Previous studies using this theory have demonstrated many of these connections, especially in multimedia studies.…”
Section: Quantitative Design and Data Analysis (Phase 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Online consumers prefer the visual demonstration of items, which makes those products appealing [ 69 ]. The relationship between attitude and intention is an extended application of the TPB [ 70 , 71 ]. Previous studies using this theory have demonstrated many of these connections, especially in multimedia studies.…”
Section: Quantitative Design and Data Analysis (Phase 2)mentioning
confidence: 99%
“…Enjoyment is defined as “a perception of the fun and enjoy activity derived from watching mukbang” [ 54 ]. Information is defined as “the extent to which mukbang contents shared in UGC can provide users with relevant and timely information” [ 70 ]. Attractiveness is defined as “the extent to which mukbang users consider mukbang content providers’ charming” [ 74 ].…”
Section: Quantitative Design and Data Analysis (Phase 2)mentioning
confidence: 99%
“…This orientation is particularly evident in the post‐pandemic era, where to promote consumption are prioritized over policies related to sustainable consumption (Taherzadeh, 2021). This is exemplified by the issuance of consumption vouchers and other policy instruments by governments aimed at incentivizing increased consumption (Dong et al, 2023; Kim & Lee, 2021; Lin & Chen, 2020). These examples introduce a rather pessimistic assertion: In favorable economic conditions, governments may heed international calls for green consumption as a testament to their environmental commitment.…”
Section: Understanding Unsustainable Consumptionmentioning
confidence: 99%
“…Currently, due to the impact of COVID-19, the tourism industry is facing severe challenges such as prominent vulnerability and increased risk uncertainty [1][2][3]. Meanwhile, there are many supplies for tourism, and the potential tourism demand is still large [4][5][6].…”
Section: Introductionmentioning
confidence: 99%